2015
DOI: 10.14393/bj-v31n6a2015-26164
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen in the production of green and dry mass and the efficiency of nitrogen conversion and apparent recovery of pearl millet cultivars

Abstract: ABSTRACT:The potential of dry (DM) and green (GM) matter yield, plant nitrogen concentration (NC), apparent nitrogen conversion efficiency (NCE) and apparent N recovery (ANR) of pearl millet cultivars with nitrogen fertilization are analyzed. Current experiment was conducted in the municipality of Ceres GO Brazil, within the Cerrado (Brazilian savannah) biome. A 3x4x2 randomized factorial block design was employed, with three repetitions. Treatments were composed of three pearl millet cultivars (ADR-7010, ADR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…The ANR was higher in ADR500 (78.76%), followed by ADR 7020 (42.68%) and LABH 70732 (21.18%) ( Table 2). This reinforces the physiological ability of this forage to absorb the available nitrogen in the soil solution as long as fertility is corrected, according to studies conducted by Silva et al (2012) and Buso et al (2015). On the other hand, the cultivars showed a difference in NCE.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The ANR was higher in ADR500 (78.76%), followed by ADR 7020 (42.68%) and LABH 70732 (21.18%) ( Table 2). This reinforces the physiological ability of this forage to absorb the available nitrogen in the soil solution as long as fertility is corrected, according to studies conducted by Silva et al (2012) and Buso et al (2015). On the other hand, the cultivars showed a difference in NCE.…”
Section: Discussionsupporting
confidence: 79%
“…The crude protein (CP) content of millet cultivars evaluated in the present study (mean of 9.54%) also resemble those found by Guimarã es Júnior et al (2010), who evaluated pearl millet genotypes for the ensiling process and found an average of 10.95% CP in the dry matter. Higher concentrations of CP in the millet crop (close to 20%) have already been reported by Silva (2012) and Buso et al (2015), but this was in a cut-off regime. Thus, the CP concentrations decrease with biomass accumulation, as a function of the maturity process of the forage crop, but this does not limit its use in animal feed.…”
Section: Discussionsupporting
confidence: 51%
“…Varietal variation in forage yield and quality is common, thus variety selection is an important management decision. Curvilinear increases in forage pearl millet yield and protein concentrations in response to nitrogen fertiliser application is common (Buso et al ., 2015; Heringer and Moojen, 2002).…”
Section: Brazilian Pearl Millet Production Systemsmentioning
confidence: 99%